Pengaruh variasi konsentrasi terhadap uji sifat fisik dan stabilitas freeze- thaw cycling pada formula sediaan gel kombinasi ekstrak daun kelor dan ekstrak daun jeruk nipis - Juliana, Intan; Fatmawati, Annisa; Munir, Muhammad Abdurrahman; Emelda, Emelda; Rahmawati, Feti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Moringa leaves are a major source of antioxidant compounds due to their high content in carotenoids, ascorbic acid, glucosinolates and other bioactives. Lime contains elements of useful chemical compounds, such as alkaloids, polysaccharides, flavonoids, and essential oils. This study aims to obtain a gel formula that is physically stable and stable during storage using the Freeze-Thaw Cycling method from Moringa leaf extract and lime leaf extract. This research is a laboratory experimental research. Gel preparation was carried out with varying concentrations of Moringa leaf extract and lime leaf extract F1 (75%:25%), F2 (50%:50%), and F3 (25%:75%). Testing the physical properties of the gel includes organoleptic, pH, homogeneity, viscosity, spreadability, adhesion and syneresis. The stability test carried out was a stability test using the Freeze-Thaw Cycling method for 3 cycles by observing the stability to be carried out where each cycle observed physical changes in the gel including organoleptic, homogeneity and pH. The results of gel preparations of the combination of ethanol extract of moringa leaves and lime leaves of formulations 1, 2, and 3 with differences in the concentration of the active substance were declared stable, because there was no significant change from organoleptic observations, homogeneity, pH, adhesion and spreadability. However, statistical tests stated that the 4℃ temperature adhesion test obtained a p value (<0.05) and a 40℃ temperature p value (>0.05), while the 4℃ and 40℃ temperature spreadability test obtained a p value (<0. 05).